Meningkatkan Sistem Pendidikan dan Gaya Hidup Menabung yang Baik serta Meningkatkan Kualitas Tempat Belajar yang Bersih, Sehat, dan Aman di Paud Al-Halim melalui Program Sosialisasi - Matondang, Joshua Ringgas; Pasaribu, Tio Ruben Efraim; Farasvania, Jane Marta; Elsadday, Jonathan; Novastradica, Fedrik Yoel (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
The KKM-PKM program at PAUD Al-Halim was designed to increase awareness of saving habits and environmental cleanliness among early childhood students. The program consisted of several activities, including material presentations on the benefits of saving, hands-on cleaning of the PAUD facilities, and distributing piggy banks to motivate the children to begin saving. These efforts were aimed at not only fostering financial awareness but also at improving the quality of the educational environment by promoting cleanliness. Throughout the month-long program, it was observed that the children showed increased engagement and understanding of both saving and hygiene practices. This was evident through their active participation in cleaning activities and their growing interest in saving. Furthermore, the educators and community leaders also became more involved in reinforcing these values in the daily routines of the children. The long-term goal of this program is to instill positive financial and hygienic habits early in life, which can contribute to the children's overall development. It is expected that this initiative will lead to healthier, more disciplined individuals, ultimately benefiting their future education and personal growth.